Hukum Transplantasi Jantung Dari Donor Non Muslim Menurut Maslahah Al-Syatibi - Ilmi, Nurul; , Prof. Dr. Harun Joko Prayitno, M.Hum; , Dr. Imron Rosyadi M.Ag (2015)
A problem that appears in doing transplantation technology has been properly handled by some medical experts, but some ethical and juridical problems seem to be unfinished. This discussion is aimed to know the law of heart transplantation that is taken from non-moslems donor based on al-Syatibi‟s benefits. Transplantation is a new case which is not showed by nash directly, that is why the proper method used in this research is by istislahi logical pattern or almashlahah theory. The theory figure that is chosen is al-Syatibi. He combines two approaches between lafadh dhahir and the opinion of meaning or 'illat in the forms of the two which do not break their definitions in order to make the syari'ah goes harmonically without contradictions. Started from a nash, how hearts are so influential to human‟s behavior, then it is strengthen by some medical experts with their researches which state the effect of transplantation toward behaviors. The medical experts state that a memory cells makes recipients act like their donors, although they never meet before. This shows the relationship between hearts and behavior which influence the law. If the recipients take the hearts from non-moslems donor, then the recipients will have the same beliefs from the previous donor. That is why ignoring the damage is more important than doing it because it will effect on suffering hereafter. That is the point of almashlahah theory.